Synthesis of new 1,2-disubstituted benzimidazole analogs as potent inhibitors of Î-Glucuronidase and in silico study - Muhammad Taha; Ahmad Khan, Aftab; Rahim, Fazal; Imran, Syahrul; Mohammed Salahuddin; Uddin, Nizam; Mohammed Khan, Khalid; Ali Shah, Syed Adnan; Zafar, Ameeduzzafar; Zakaria, Zainul Amiruddin (Elsevier B.V., 2021)
New benzimidazole analogues (1–18) were synthesized and characterized through different spectroscopic techniques such as 1H NMR, 13C NMR and HREI-MS. All analogues were screened for β-glucuronidase inhibitory potential. All analogues showed varied degree of inhibitory potentials with IC50 values ranging between 1.10 ± 0.10 to 39.60 ± 0.70 μM when compared with standard D-saccharic acid-1,4- lactone having IC50 value 48.30 μM. Analogues 17, 11, 9, 6, 1 and 13 having IC50 values 1.10 ± 0.10, 1.70 ± 0.10, 2.30 ± 0.10, 5.30 ± 0.20, 6.20 ± 0.20 and 8.10 ± 0.20 μM respectively, showed excellent β-glucuronidase inhibitory potential many folds better than the standard. All other analogues also showed good inhibitory potential better as compared to standard. Structure activity relationships (SAR) has been established for all compounds. The results from molecular docking studies supports the established SAR and developed a strong correlation with the results from in to vitro assay. The molecular docking results clearly highlighted how substituents like nitro and chloro affect the binding position of the active compounds in the active site. The docking results were also used to properly establish the effect of bulky substituents of least active compounds on reduced β-glucuronidase inhibitory activity. Compounds 1–18 were found non-toxic.